Prevalence of atrial fibrillation and association of previous antithrombotic treatment in patients with cerebral microbleeds. (30th December 2014) - Horstmann, S.; Möhlenbruch, M.; Wegele, C.; Rizos, T.; Laible, M.; Rauch, G.; Veltkamp, R.
Abstract : Background and purpose: Cerebral microbleeds (CMBs) are associated with an increased risk of intracerebral hemorrhage. The impact of oral anticoagulation (OAC) on CMBs is not well characterized. Our aim was to assess the prevalence of CMBs in stroke and transient ischaemic attack (TIA) patients with atrial fibrillation (AF) and to analyze the implications of previous treatment with OAC. Methods: In this retrospective analysis on data from a prospectively recruiting stroke registry, patients with ischaemic stroke or TIA with brain magnetic resonance imaging including susceptibility weighted imaging were consecutively enrolled during a 3‐year period. For each patient cardiovascular risk factors, AF history and recent diagnosis of AF, present use of OAC and antiplatelets, the National Institute of Health Stroke Scale and the premorbid modified Rankin Scale score were recorded. Two independent raters identified CMBs according to consensus criteria. CMB location was classified as lobar, deep or in the posterior fossa. Results: In all, 785 patients (mean age 63.9 ± 14.2 years) were included. At least one CMB was detected in 186 (23.7%) patients. CMBs were significantly more frequent in patients with AF (30.5% vs. 22.4%). Patients with previous OAC treatment were more likely to have CMBs (36.7% vs. 22.8%, P = 0.03) and abundant CMBs ( n > 10) were more frequent in anticoagulated patients even after adjustment for age. However, age was the only independent factor predicting CMBs ( P = 0.001). Conclusions: Cerebral microbleeds are common in elderly AF patients with acute ischaemic stroke. Previous OAC is associated with a higher number of CMBs predominantly in the lobar location. Establishing a causal relationship requires prospective longitudinal investigation. Abstract : Clickhere to view the accompanying paper in this issue.